STRATEGI MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMK NEGERI 1 TANJUNG RAYA KABUPATEN AGAM - Etiya Putri; Charles; Wedra Aprison; Muhiddinur Kamal (Universitas Pahlawan Tuanku Tambusai, 2022)
Based on the observations made by the researchers, it is known that the strategy of Islamic religious education teachers in increasing the learning motivation of class X TM students at SMK Negeri 1 Tanjung Raya, Agam Regency. The purpose of this study was to find out how the teacher's strategy in increasing the learning motivation of class X TM 1 students at SMK Negeri 1 Tanjung Raya, Agam Regency. This study uses a descriptive qualitative approach with the key informants are Islamic religious education teachers, and the supporting informants are students of class X TM and the principal. In collecting data, the researcher used observation and interview methods. The data analysis technique that the author uses is data reduction, data display, and conclusions. To test the validity of the data, researchers used data triangulation techniques. Based on the research that has been done, the strategy of PAI teachers in increasing student motivation in Islamic religious education subjects for class X TM at SMK Negeri 1 Tanjung Raya has been carried out but has not been maximized. Thus the PAI teacher's strategy in increasing student learning motivation is to use learning methods that attract students' attention, use cooperative learning models, understand the characteristics of class X TM students, use learning media that attract students' attention, and form a conducive and fun learning climate. Another strategy is to give grades and hold competitions to make students active and increase students' motivation to learn in Islamic religious education subjects. Keyword: Strategy, Learning Motivation, Islamic Religious Education